Fostering positive changes in health and social relationships in children - Lozada, Mariana (2017)
Several studies have demonstrated that altruism and gratitude may confer beneficial effects on psychophysical wellbeing. The present chapter describes how positive changes in health and social relationships can be fostered in 6- to 9-year-old chil-dren when participating in positive interventions. The findings show that the experi-ence of working with others to attain shared goals and focusing on gratefulness posi-tively modulated altruism and social interactions among peers, highlighting the great behavioural plasticity of children. Moreover, interventions involving coopera-tive playing not only increased positive relationships but also contributed to a de-crease in chronic stress levels. The positive outcomes of participating in the de-scribed interventions were assessed by means of quantitative methods, such as phys-iological parameters, sociometric measures and tests of altruism, the use of which, to our knowledge, has not been thoroughly explored in children. The present find-ings tie in well with the hypothesis that altruism is an embodied and situated human resource, which can convey intrinsic benefits. Furthermore, results from the studies mentioned indicate that positive transformations can be easily fostered through the performance of this type of intervention. Given that schools provide a stimulating environment that significantly influences children’s development, our findings high-light the benefits of working in this way to promote positivity in formal educational contexts, which could certainly contribute to the enhancement of individual and social wellbeing.